(untitled) (Bioagro, 2025)
Uvina is one of the eight grape varieties permitted for the production of pisco in Peru and is part of the country’s cultural heritage. However, the effect of rootstocks on its properties has not been widely studied. The influence of different rootstocks on the morpho-productive characteristics of Uvina from the INIA Germplasm Bank was evaluated, considering fourteen qualitative traits. Descriptive analyses were performed, as well as ANOVA with comparison of means using the Tukey test (P < 0.05). For nonparametric tests, the Kruskal-Wallis test with Holm post hoc test (P < 0.05), in addition to Pearson correlation and principal components analyses. The results showed that the Salt Creek and 5BB rootstocks stood out for presenting the highest number and mass of bunches per plant, as well as greater internode length and shoot mass. Paulsen showed intermediate performance, while MGT recorded the lowest values in most of the variables analyzed, with the exception of total soluble solids content, a parameter in which it outperformed the others. It is concluded that the rootstocks significantly influenced the morphological and productive characteristics of the Uvina.